Citra Diri Pada Perempuan Berhijab Pengguna Rokok Elektrik - Mutia Mawardah; Imam Budi Darma (Jurnal Ilmiah Psyche, 2021)
Abstract : This study aims to look at the self-image of female adolescents wearing e-cigarette wearing hijab. What factors affect the self-image of women who use e-cigarette wearing hijab, as well as how the self-image of women wearing e-cigarette wearing hijabs. This study uses a qualitative research design and uses a phenomenological approach to be able to see the self-image of women who use e-cigarettes. In this study, researchers used 6 sources. 2 people as research subjects, 2 people as the perpetrator informant and 2 informants know of each subject. The results of this study found that the self-image of the e-cigarette wearing hijab woman who has a self-image that is not much different. The first subject has four self-images, while the second subject also has four self-images from four self-image images. Each description that is owned by the subject is also based on several factors, namely physical condition, family condition, seeking attention, depending on smoking and expectations. Keywords: Self Image, Electric Cigarette, Female Wearing Hijab Abstrak : Penelitian ini bertujuan untuk mengetahui citra diri remaja perempuan berhijab pengguna aktif rokok elektrik. Faktor apa saja yang mempengaruhi citra diri perempuan berhijab pengguna rokok elektrik, serta bagaimana gambaran citra diri perempuan berhijab pengguna rokok elektrik. Penelitian ini menggunakan desain penelitian kualitatif serta menggunakan pendekatan fenomenologi untuk dapat mengetahui citra diri perempuan berhijab pengguna rokok elektrik. Dalam penelitian ini, peneliti menggunakan 6 sumber. 2 orang sebagai subjek penelitian, 2 orang sebagai informan pelaku dan 2 orang informan tahu dari masing-masing subjek. Hasil penelitian ini menemukan bahwa citra diri perempuan berhijab pengguna rokok elektrik memiliki citra diri yang tidak jauh berbeda. Subjek pertama memiliki empat citra diri, sementara subjek kedua juga memiliki empat citra diri dari empat gambaran citra diri. Setiap gambaran yang dimiliki oleh subjek juga dipengaruhi oleh beberapa faktor yaitu keadaan fisik, teman sebaya dan kelompok, keadaan keluarga, mencari perhatian, ketergantungan merokok dan harapan. Kata kunci: Citra Diri, Rokok Elektrik, Wanita Berhijab